Progress of the world's women 2015-2016 transforming economies, realizing rights (UN Women, 2015)
"This Report focuses on the economic and social dimensions of gender equality, including the right of all women to a good job, with fair pay and safe working conditions, to an adequate pension in older age, to health care and to safe water without discrimination based on factors such as socio-economic status, geographic location and race or ethnicity. In doing so, it aims to unravel some of the current challenges and contradictions facing the world today: at a time when women and girls have almost equal opportunities when it comes to education, why are only half of women of working age in the labour force globally, and why do women still earn much less than men? In an era of unprecedented global wealth, why are large numbers of women not able to exercise their right to even basic levels of health care, water and sanitation?"--Page 11.